PENGARUH SENAM NIFAS “OTARIA” TERHADAP KECEPATAN INVOLUSI UTERI PADA IBU POST PARTUM DI WILAYAH KERJA PKM SAYUNG 2 KABUPATEN DEMAK - Susi Susanti; Kristina Maharani; Siti Juwariyah (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
It is estimated that 60% of deaths in pregnancy occur after delivery and 50% of deaths postpartum within the first 24 hours. After the baby is born, the uterus which during labor contracts and retracts will become hard so that it can close the large blood vessels that lead to the former implantation of the placenta. If the involution process does not go well, a condition called uterine sub involution will arise. If the sub involution of the uterus is not handled properly, it will result in bleeding, for that the mother needs certain exercises that can accelerate the process of involution. According to several studies, to speed up the process of uterine involution, one of the recommended exercises is postpartum gymnastics, an integration model of relaxation techniques and exercises for the 'Otaria' abdominis muscles. The purpose of this study was to determine whether postpartum exercise model integration of relaxation techniques and 'Otaria' abdominis muscle exercises had an effect on the speed of uterine involution in post partum mothers at PKM Sayung 2, Demak Regency. This study uses a quantitative approach, the method used in this study is a quasi-experimental or quasi-experimental. The design used in this study was Post-test Only Control Group Design. Data analysis used univariate analysis and bivariate analysis. The results showed that respondents who did puerperal exercise 'otaria' experienced uterine involution faster than respondents who did postpartum exercise with a value of (p-value <0.05) at TFU and (p-value <0.05) at lochia. Keywords: Otaria Postpartum Gymnastics, Uterine Involution Speed